Blockchain in international e-government processes: Opportunities for recognition of foreign qualifications. (December 2021) - Pauletto, Christian
Abstract: Purpose: Recognition of foreign qualifications for authorising the exercise of a regulated profession gains importance in globalised economies and in international organisations such as the UNESCO. However, national procedures for such recognition have not yet experienced the transformative changes that occurred in other sectors of public administration. The study of "transborder digitisation" is still in its infancy. While governments consider the adoption of blockchain applications for the e-administration of trade-related procedures, for example customs procedures, it is timely to give some thoughts to recognition as well. Aims: After explaining the role of recognition in international relations this article explores the features of recognition procedures that are relevant for the choice of a technology. It then aims to identify recognition authorities' needs in terms of administrative tools and to find out the options and potential benefits of blockchain technology in view of those needs. It aims to find whether there are reasons to select that particular technology rather than conventional methods. This is highlighted in a concrete description of what could be a possible configuration of a blockchain solution for recognition procedures. Since opportunities are always balanced by limitations, the article also inquires into ithe expected challenges in adopting a blockchain system between different countries' recognition authorities. The article's overall aim is to offer an assessment of blockchain technologies' potential in that field and to highlight developments in technology that could ease their adoption. Findings: The article finds that the advantages brought by DLT technologies and the needed features of recognition processes coincide in several respects. However, some critical challenges and limitations for the application of blockchain in this field also exist. An adoption of that technology for that particular branch of public administration could occur provided that the technology continues to improve. Such improvements include interoperability, interface with other protocols and legacy databases, portability, and a higher degree of safety regarding privacy.